2018
DOI: 10.1073/pnas.1722505115
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric shear banding and swarming vortices in bacterial superfluids

Abstract: Bacterial suspensions-a premier example of active fluids-show an unusual response to shear stresses. Instead of increasing the viscosity of the suspending fluid, the emergent collective motions of swimming bacteria can turn a suspension into a superfluid with zero apparent viscosity. Although the existence of active superfluids has been demonstrated in bulk rheological measurements, the microscopic origin and dynamics of such an exotic phase have not been experimentally probed. Here, using high-speed confocal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
58
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 39 publications
(66 reference statements)
6
58
1
1
Order By: Relevance
“…The generalized active gel model proposed in this work has allowed us to perform a fully 2d analysis, by keeping under control the time evolution of the important variables, such as the local concentration and the orientation of the active constituents. Thus we confirmed, by varying both external and internal forcing, the existence of superfluidic and negative viscosity states found experimentally in bacterial suspensions 36,37 whose first numerical confirmation by means of quasi-1d simulations was furnished in 40 . Moreover, we also found that a maximum entropy production principle holds in selecting the most probable state in the intermittent viscosity regime.…”
Section: Overview Phase Diagram and Conclusionsupporting
confidence: 81%
See 1 more Smart Citation
“…The generalized active gel model proposed in this work has allowed us to perform a fully 2d analysis, by keeping under control the time evolution of the important variables, such as the local concentration and the orientation of the active constituents. Thus we confirmed, by varying both external and internal forcing, the existence of superfluidic and negative viscosity states found experimentally in bacterial suspensions 36,37 whose first numerical confirmation by means of quasi-1d simulations was furnished in 40 . Moreover, we also found that a maximum entropy production principle holds in selecting the most probable state in the intermittent viscosity regime.…”
Section: Overview Phase Diagram and Conclusionsupporting
confidence: 81%
“…Experiments 33,34 and further theories 35 confirmed that extensile active components are able to lower the viscosity of thin film suspensions. An effective inviscid flow was observed in 36 and more recently in 37 , when the concentration and activity of E. Coli are sufficiently large to support coherent collective swimming. A related feature in extensile gels is the appearance of persistent uni-directional flows in experiments on bacterial suspensions 38 and ATP-driven gels 39 .…”
Section: Introductionmentioning
confidence: 94%
“…In particular, the so-called "superfluidity regime" of vanishing and then negative effective viscosity (13) predicted by theory (14) remains mysterious. Indirect observations imply a possible connection with the emergence of large-scale collective motion (15). The latter is expected by continuum kinetic theory (CKT) to be strongly affected by confinement (16,17).…”
mentioning
confidence: 99%
“…An example is the reduction of the apparent viscosity of bacterial suspensions under shear [16][17][18][19][20][21] . Remarkably, upon increasing activity, the apparent viscosity can decrease until a value of zero is achieved, giving rise to superfluid-like behaviour 20,22 . In the last decade, rheological measurements [16][17][18][19][20] have shown qualitative agreement with earlier theoretical predictions [23][24][25][26][27][28] for the macroscopic mechanical properties of active suspensions.…”
Section: Introductionmentioning
confidence: 99%
“…Yet a more thorough understanding of the underlying mechanisms driving these systems requires a more quantitative comparison of theoretical models with experiments 29 . Such a comparison is becoming possible as more detailed information, such as transient rheological behaviour 20 and velocity profiles 22 , becomes accessible experimentally.…”
Section: Introductionmentioning
confidence: 99%